Determination of the Prevalence of Triazole Resistance in Environmental Aspergillus fumigatus Strains Isolated in South Wales, UK - Tsitsopoulou, Alexandra; Posso, Raquel; Vale, Lorna; Bebb, Scarlett; Johnson, Elizabeth; White, P. L. (Frontiers in Microbiology, 2018)
Background/Objectives Azole resistance in Aspergillus fumigatus associated with the TR34/L98H mutations in the cyp51A gene have been increasingly reported. Determining the environmental resistance rate has been deemed important when considering front-line therapy for invasive aspergillosis. The aim of the study was to determine prevalence of azole resistance in environmental A. fumigatus isolates across South Wales. Methods Over five months in 2015, 513 A. fumigatus isolates were cultured from 671 soil and 44 air samples and were screened for azole resistance using VIP agar plates containing itraconazole, voriconazole and posaconazole. Resistance was confirmed by the CLSI M38-A2 methodology. The mechanism of resistance was investigated using the PathoNostics AsperGenius Assay. Results Screening by VIP plate identified azole-resistance in 30 isolates most of which (28/30) harboured the TR34/L98H mutation, generating a prevalence of 6.0%. Twenty-five isolates had a MIC of ≥2mg/L with itraconazole, 23 isolates had a MIC of ≥2mg/L with voriconazole and seven isolates had a MIC ≥0.25mg/L with posaconazole. All isolates deemed resistant by VIP plates were resistant to at least one azole by reference methodology. Conclusions There is significant environmental azole resistance (6%) in South Wales, in close proximity to patients susceptible to aspergillosis. Given this environmental reservoir, azole resistance should be routinely screened for in clinical practice and environmental monitoring continued.